The Seven Deadly Virtues - Lynn Z. Bloom (Journal of the Assembly for Expanded Perspectives on Learning, 2004)
The university stifles most creative writers except the most intrepid—even reckless, the good along with the bad—in the process of teaching them to write according to the conventions of the academy in general, and their specific disciplines in particular.